Estimation of nocturnal CO2 and N2O soil emissions from changes in surface boundary layer mass storage - R. H. Grant; R. A. Omonode (Atmospheric Measurement Techniques, 2018)
Annual budgets of greenhouse and other trace gases require knowledge of the emissions throughout the year. Unfortunately, emissions into the surface boundary layer during stable, calm nocturnal periods are not measurable using most micrometeorological methods due to non-stationarity and uncoupled flow. However, during nocturnal periods with very light winds, carbon dioxide (CO2) and nitrous oxide (N2O) frequently accumulate near the surface and this mass accumulation can be used to determine emissions. Gas concentrations were measured at four heights (one within and three above canopy) and turbulence was measured at three heights above a mature 2.5 m maize canopy from 23 July to 10 September 2015. Nocturnal CO2 and N2O fluxes from the canopy were determined using the accumulation of mass within a 6.3 m control volume and out the top of the control volume within the nocturnal surface boundary layer. Diffusive fluxes were estimated by flux gradient method. The total accumulative and diffusive fluxes during near-calm nights (friction velocities < 0.05 ms−1) averaged 1.16 µmol m−2 s−1 CO2 and 0.53 nmol m−2 s−1 N2O. Fluxes were also measured using chambers. Daily mean CO2 fluxes determined by the accumulation method were 90 to 130 % of those determined using soil chambers. Daily mean N2O fluxes determined by the accumulation method were 60 to 80 % of that determined using soil chambers. The better signal-to-noise ratios of the chamber method for CO2 over N2O, non-stationary flow, assumed Schmidt numbers, and anemometer tilt were likely contributing reasons for the differences in chambers versus accumulated nocturnal mass flux estimates. Near-surface N2O accumulative flux measurements in more homogeneous regions and with greater depth are needed to confirm the conclusion that mass accumulation can be effectively used to estimate soil emissions during nearly calm nights.